OPPORTUNITIES TO ADVANCE INDONESIA'S ECONOMY THROUGH THE OECD AND BRICS - Alia Rahmatulummah; Bagas Rizky Ramadhan; Inas Alya Naura (Budi Luhur Journal of Strategic & Global Studies, 2025)
Abstract: Indonesia's membership in the Organisation for Economic Co-operation and Development (OECD) and BRICS (Brazil, Russia, India, China, South Africa) is a strategic step to strengthen itse conomic and political position on the global stage. In facing globalc hallenges such as the COVID-19 pandemic and commodity pricef luctuations, involvement in these two organizations is expected to provide significant benefits for economic growth and national development. Joining the OECD provides access to best practicesand international standards, which can enhance the quality of public policies and Indonesia's economic reputation. Meanwhile, membership in BRICS offers opportunities to expand export markets and increase cooperation with other developing countries. Despite challenges, such as economic disparities among BRICS members and the need to improve the competitiveness of national products, this move reflects a pragmatic approach in Indonesia's foreign policy. By leveraging opportunities from both organizations, Indonesia can accelerate its economic transformation and achieve the status of a developed nation in line with the vision of Indonesia Gold 2045.  Abstrak: Keanggotaan Indonesia dalam Organisation for Economic Co-operation and Development (OECD) dan BRICS (Brazil, Rusia, India, China, Afrika Selatan) merupakan langkah strategis untuk memperkuat posisi ekonomi dan politik di kancah global. Dalam menghadapi tantangan global seperti pandemi COVID-19 dan fluktuasi harga komoditas, keterlibatan dalam kedua organisasi ini diharapkan dapat memberikan manfaat signifikan bagi pertumbuhan ekonomi dan pembangunan nasional. Bergabung dengan OECD memberikan akses ke praktik terbaik dan standar internasional, yang dapat meningkatkan kualitas kebijakan publik dan reputasi ekonomi Indonesia. Sementara itu, keanggotaan dalam menawarkan peluang untuk memperluas pasar ekspor dan meningkatkan kerjasama dengan negara-negara berkembang lainnya. Meskipun terdapat tantangan, seperti ketimpangan ekonomi antar anggota BRICS dan kebutuhan untuk meningkatkan daya saing produk nasional, langkah ini mencerminkan pendekatan pragmatis dalam politik luar negeri Indonesia. Dengan memanfaatkan peluang dari kedua organisasi ini, Indonesia dapat mempercepat transformasi ekonomi dan mencapai status negara maju sesuai dengan visi Indonesia Emas 2045.